2019
DOI: 10.3390/nano9060888
|View full text |Cite
|
Sign up to set email alerts
|

NanoTiO2 Sunscreen Does Not Prevent Systemic Oxidative Stress Caused by UV Radiation and a Minor Amount of NanoTiO2 is Absorbed in Humans

Abstract: The present pilot study tested the efficiency of nanoTiO2 sunscreen to prevent the oxidative stress/inflammation caused by ultraviolet (UV) radiation using biomarkers in subjects’ blood, urine, and exhaled breath condensate (EBC). In addition, the skin absorption of nanoTiO2 was studied. Six identical subjects participated in three tests: (A) nanoTiO2 sunscreen, (B) UV radiation, and (C) sunscreen + UV. The first samples were collected before the test and the second after sunscreen application and/or UV exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…It was shown that the skin absorption of nanoTiO 2 already occurs after the first 6 hours of exposure, although in a small quantity (19). This agrees with the histological proof of nanoTiO 2 particles in the viable cells of both the epidermis and dermis in the study by Tan et al (26).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…It was shown that the skin absorption of nanoTiO 2 already occurs after the first 6 hours of exposure, although in a small quantity (19). This agrees with the histological proof of nanoTiO 2 particles in the viable cells of both the epidermis and dermis in the study by Tan et al (26).…”
Section: Discussionsupporting
confidence: 83%
“…Two subjects reported allergic rhinitis without treatment, and one woman was being treated with thyroxin for hypothyroidism and with local corticosteroids for bronchial asthma; these subjects also participated in the previous study (19). No subject had symptoms of an acute viral disease, chronic bronchitis, or dyspnoea.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While inhalation may be the primary route for TiO 2 exposure in the workplace, in non-occupational settings Ti concentrations in air are very low, in the range of 0.01-0.1 lg/m 3 , resulting in a maximum exposure through inhalation of only 1 lg Ti/day (WHO 1982). Most dermal exposure studies, whether in vitro, ex vivo or in vivo, report that TiO 2 particles do not penetrate the (intact) skin (Crosera et al 2015;Shi et al 2013), or that only minor amounts of nano TiO 2 are absorbed in humans (Pelclova et al 2019). Medical implants have a strongly bound oxide layer which makes them inert, however, due to corrosion a Ti implant surface can be a potential source for the release of micro-and nano-sized particles (Frisken et al 2002;Sarmiento-Gonzalez et al 2009).…”
Section: Discussionmentioning
confidence: 99%